Negative electrode binder composition, negative electrode sheet, and secondary battery
By introducing a binder polymer with a specific structure into the negative electrode slurry of lithium-ion batteries, the problem of electrode bonding failure caused by SBR floating is solved, the peeling force of the electrode and the slurry stability are improved, and the battery production efficiency and electrode consistency are improved.
Patent Information
- Application Number
- CN202510910445.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-09-23
- Estimated Expiration
- 2045-07-02
AI Technical Summary
The floating of styrene-butadiene rubber (SBR) in the existing lithium-ion battery negative electrode slurry causes electrode bonding failure, affecting production efficiency and bonding strength, and easily sticks to the pressure roller, resulting in poor electrode consistency.
A first binder polymer containing aromatic vinyl structural units and conjugated diene structural units, and a second binder polymer containing ionic, acrylate and/or amide units are used to inhibit SBR from floating and improve dispersibility and bonding performance through the repulsion of similar charges and enhanced mechanical strength.
Effectively inhibit SBR floating, enhance the electrode peeling force and slurry stability, improve the electrode consistency, and improve production efficiency and battery cycle performance.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode binder composition, a negative electrode sheet, and a secondary battery. Background Art
[0002] Lithium-ion batteries have become the main power source of choice for modern portable electronic devices, electric vehicles and energy storage systems due to their advantages such as high energy density, long cycle life and low self-discharge rate.
[0003] Binders are commonly added to the negative electrode slurry for lithium-ion batteries to improve the peel strength of the negative electrode sheet. The binder in the negative electrode slurry must effectively disperse the main material and conductive agent. Uneven dispersion can easily lead to slurry clogging, difficulty screening, and sedimentation, resulting in poor slurry stability. This can lead to uneven coating, poor coating appearance, poor electrode consistency, low capacity, and lithium deposition in the negative electrode. Currently, styrene-butadiene rubber (SBR) is commonly added to the negative electrode slurry to improve electrode sheet processing, prevent cracking, and further enhance peel strength. However, after the slurry is applied and the electrode sheet is baked, the SBR floats up as the water evaporates, resulting in uneven distribution of the binder within the electrode sheet and causing bond failure. Furthermore, SBR is relatively soft, and this floating SBR can easily stick to the rollers during electrode sheet pressing, causing sticking and impacting electrode sheet production efficiency.
[0004] Therefore, there is an urgent need for a new type of negative electrode binder to improve the production efficiency of the electrode and the bonding strength of the binder in the electrode. Summary of the Invention
[0005] The present invention aims to solve the problem that the existing negative electrode cannot effectively suppress the electrode sheet bonding failure caused by the floating of styrene-butadiene rubber. The present invention provides a negative electrode binder composition, a negative electrode sheet, and a secondary battery.
[0006] In order to solve the above technical problems, the present invention provides a negative electrode binder composition, which includes a first binder polymer and a second binder polymer, wherein the first binder polymer includes an aromatic vinyl structural unit and a conjugated diene structural unit; the second binder polymer includes the following structural units: a. an ionic unit; b. an acrylate unit and / or an amide unit.
[0007] Preferably, the second binder polymer comprises the following structural units: a, an ionic unit; b, an acrylate unit or an amide unit; the mass ratio of the a unit to the b unit is (1-4): (6-9).
[0008] Preferably, the second binder polymer comprises the following structural units: a. ionic units; b. acrylate units and amide units; the mass ratio of the ionic units, the acrylate units and the amide units is (1-4): (2-6): (2-6).
[0009] Preferably, the weight average molecular weight of the second binder polymer is 5*10 4 -90*10 4 g / mol, and the dispersibility index of the second binder polymer is 1.2-3.
[0010] Preferably, the mass ratio of the first binder polymer to the second binder polymer is (0.5-3):(2-3).
[0011] Preferably, the ionic unit is a structural unit obtained by polymerization of an ionic monomer containing a double bond and a charge, and the ionic monomer includes one or more of sodium vinyl sulfonate, sodium vinyl phosphate, vinyl imidazole salt, sodium acrylate, sodium allyl sulfonate, dimethylaminoethyl methacrylate, sodium 2-acrylamide-2-methylpropane sulfonate, and methacryloyloxyethyltrimethylammonium chloride.
[0012] Preferably, the acrylate unit is a structural unit obtained by polymerization of acrylate monomers, and the acrylate monomers include one or more of methyl acrylate, ethyl acrylate, propyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, n-hexyl acrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate.
[0013] Preferably, the amide units are structural units obtained by polymerization of amide monomers, and the amide monomers include one or more of acrylamide, dimethylacrylamide, methacrylamide, caprolactam, isobutoxymethylacrylamide, and diacetone acrylamide.
[0014] In a second aspect, the present application provides a negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises any one of the above-mentioned negative electrode binder compositions.
[0015] In a third aspect, the present application provides a secondary battery comprising the negative electrode sheet as described above.
[0016] In the present application, an ionic unit is introduced into the second binder polymer, and the repulsion of charges of the same nature is utilized to promote the stretching of the linear molecular chain of the second binder polymer, thereby improving the dispersion ability of the various components of the negative electrode slurry, improving the stability of the negative electrode slurry, and being beneficial to the processing of the negative electrode slurry and the negative electrode sheet, improving the consistency of the electrode sheet, and suppressing the problem of negative electrode lithium precipitation. At the same time, the ionic unit in the second binder polymer can disperse SBR well, form a good traction effect with SBR, suppress the floating of SBR, thereby improving the peeling force of the electrode sheet, and suppressing the problem of the binder sticking to the roller when the electrode sheet is rolled. Furthermore, by introducing acrylate units and / or amide units into the second binder polymer, the mechanical strength of the second binder polymer is improved, and the bonding performance of the negative electrode binder composition is further improved. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] An embodiment of the present application provides a negative electrode binder composition, which includes a first binder polymer and a second binder polymer. The first binder polymer includes an aromatic vinyl structural unit and a conjugated diene structural unit. Specifically, the first binder polymer is styrene-butadiene rubber; the second binder polymer includes the following structural units: a. an ionic unit; b. an acrylate unit and / or an amide unit.
[0019] In this embodiment, an ionic unit is introduced into the second binder polymer, and the repulsion of like-charged substances is utilized to promote the stretching of the linear molecular chain of the second binder polymer, thereby improving the dispersion ability of the various components of the negative electrode slurry, improving the stability of the negative electrode slurry, and facilitating the processing of the negative electrode slurry and the negative electrode sheet, improving the consistency of the electrode sheet, and suppressing the problem of negative electrode lithium precipitation. At the same time, the ionic unit in the second binder polymer can well disperse SBR, form a good traction effect with SBR, suppress the floating of SBR, thereby improving the peeling force of the electrode sheet, and suppressing the problem of the binder sticking to the roller when the electrode sheet is rolled. Furthermore, by introducing acrylate units and / or amide units into the second binder polymer, the mechanical strength of the second binder polymer is improved, and the bonding performance of the negative electrode binder composition is further improved.
[0020] In some embodiments, the second binder polymer comprises the following structural units: a, an ionic unit; b, an acrylate unit or an amide unit; the mass ratio of units a to b is (1-4):(6-9). It is understood that the second binder polymer comprises ionic units and acrylate units, or the second binder polymer comprises ionic units and amide units, and the copolymer formed by the ionic units and the acrylate units or amide units is a block-type second binder polymer. Specifically, the mass ratio of units a to b includes, but is not limited to, 1:9, 1:6, 2:8, 2:5, 3:7, 3:9, 4:6, or 4:9. By limiting the mass ratio of units a to b in the second binder polymer, the linear molecular chain of the second binder polymer is ensured to be stretched, thereby improving the dispersion performance of the negative electrode binder composition in the negative electrode slurry and its traction effect on SBR.
[0021] In some embodiments, the second binder polymer comprises the following structural units: a) an ionic unit; b) an acrylate unit and an amide unit; the mass ratio of the ionic unit, the acrylate unit, and the amide unit is (1-4):(2-6):(2-6). The mass ratio of the ionic unit, the acrylate unit, and the amide unit includes, but is not limited to, 1:2:6, 1:6:6, 1:4:6, 2:3:5, 2:3:3, 3:6:2, 3:6:4, 4:3:3, 4:2:4, 2:2:6, 2:5:3, 2:6:2, 1:4:5, 1:6:3, or 1:5:4. By limiting the mass ratio of the ionic unit, the acrylate unit, and the amide unit, on the one hand, the linear molecular chain of the second binder polymer is stretched, thereby improving the dispersion performance of the negative electrode binder composition in the negative electrode slurry and the traction effect on SBR. Furthermore, by controlling the content of acrylate and amide units, the mechanical strength of the second binder polymer is regulated, ensuring the adhesive properties of the negative electrode binder composition. Acrylate units act as internal plasticizers within the binder, reducing its crystallinity and increasing its flexibility. Amide units have strong polarity, enhancing the binder's adhesion to the host material and metal foil. Furthermore, amide units possess significant rigidity, contributing to the binder's stiffness. The simultaneous addition of acrylate and amide units modulates the binder's mechanical properties and improves its flexibility.
[0022] In some embodiments, the weight average molecular weight of the second binder polymer is 5*10 4 -90*10 4g / mol, and the dispersion index (PDI) of the second binder polymer is 1.2-3. It is understood that if the low molecular weight portion of the second binder polymer is too high, it will be easily swollen or degraded by the electrolyte, releasing small molecules and reducing the battery's cycle life. If the molecular weight of the second binder polymer is too high, it can easily lead to poor flowability of the negative electrode slurry and uneven electrode coating thickness.
[0023] In some embodiments, the mass ratio of the first binder polymer to the second binder polymer is (0.5-3):(2-3). By limiting the mass ratio of the first binder polymer to the second binder polymer, the second binder polymer can better suppress the floating of the SBR, thereby achieving the effect of improving the electrode peeling force.
[0024] In some embodiments, the ionic unit is a structural unit obtained by polymerization of an ionic monomer containing a double bond and a charge, and the ionic monomer includes one or more of sodium vinyl sulfonate, sodium vinyl phosphate, vinyl imidazole salt, sodium acrylate, sodium allyl sulfonate, dimethylaminoethyl methacrylate, sodium 2-acrylamido-2-methylpropanesulfonate, and methacryloyloxyethyltrimethylammonium chloride. By selecting such charged ionic monomers, the second binder polymer can be more highly dispersed in SBR, thereby suppressing SBR flotation.
[0025] In some embodiments, the acrylate units are structural units obtained by polymerization of acrylate monomers, including one or more of methyl acrylate, ethyl acrylate, propyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, n-hexyl acrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate. By selecting these acrylate monomers, the second binder polymer has a linear molecular chain, ensuring the mechanical strength of the second binder polymer and improving the adhesive properties of the binder.
[0026] In some embodiments, the amide units are structural units derived from the polymerization of amide monomers, including one or more of acrylamide, dimethylacrylamide, methacrylamide, caprolactam, isobutoxymethylacrylamide, and diacetoneacrylamide. By selecting these amide monomers, the second binder polymer possesses linear molecular chains, ensuring mechanical strength and improving the adhesive properties of the binder.
[0027] Furthermore, an embodiment of the present application provides a method for preparing a second binder polymer, comprising the following steps:
[0028] Ionic monomers and acrylate monomers or amide monomers are added to an aqueous solution. An initiator is then added to the aqueous solution, and the monomers are copolymerized in the aqueous solution to produce a block-type second binder polymer. The total monomer concentration is 10%-50%, the reaction time is 2-8 hours, and the reaction temperature is 45-75°C.
[0029] Ionic monomers, acrylate monomers, and amide monomers are added to an aqueous solution. An initiator is then added to the aqueous solution, and the monomers are copolymerized in the aqueous solution to produce a random second binder polymer. The total monomer concentration is 10%-50%, the reaction time is 2-8 hours, and the reaction temperature is 45-75°C.
[0030] The initiator includes one or more of ammonium persulfate, potassium persulfate, sodium persulfate, sodium bisulfite, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisopropylimidazoline, and azobiscyanovaleric acid. The amount of the initiator added is 0.5% to 1.2% of the total weight of the monomers.
[0031] As known to those skilled in the art, the reactions in the above steps are conventional free radical polymerization, etc., and the specific methods and reaction conditions are free radical polymerization methods commonly used in the prior art, which will not be described in detail in the present invention.
[0032] One embodiment of the present invention further provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises any one of the above-mentioned negative electrode binder compositions.
[0033] Furthermore, the negative electrode active material layer further includes a negative electrode active material and a negative electrode conductor.
[0034] Specifically, the mass ratio of the second binder polymer, the first binder polymer, the negative electrode active material, and the negative electrode conductive agent is (0.5-3):(4.5-2):(90-93):(2-5).
[0035] Preferably, when the active material in the negative electrode active material layer is silicon carbon or silicon, the binder composition of the above embodiment can provide sufficient binding force to buffer and suppress the volume change of silicon negative electrode material particles.
[0036] An embodiment of the present invention further provides a secondary battery, comprising the negative electrode sheet as described above.
[0037] The present invention is further described below with reference to the following examples.
[0038] The negative electrode binder, negative electrode, and secondary battery disclosed in the present invention are specifically described.
[0039] Example 1
[0040] The negative electrode binder composition includes a first binder polymer comprising SBR.
[0041] The second binder polymer is prepared as follows: sodium vinyl sulfonate and acrylamide are reacted in an aqueous solution at a mass ratio of 2:8 by free radical polymerization to obtain a block second binder polymer of sodium vinyl sulfonate and acrylamide. The synthesis initiator is potassium persulfate, the initiator addition amount is 0.5%, the monomer concentration is 13%, the reaction time is 5 hours, the reaction temperature is 60°C, and the molecular weight of the obtained polymer is 60*10 4 , a block-type second binder polymer with a PDI of 2.13.
[0042] The negative electrode sheet preparation method is as follows: the second binder polymer, SBR, silicon negative electrode, and conductive agent super P are blended in a mass ratio of 1.7:3.3:96:1 to obtain a blended powder, and the powder is blended with deionized water in a ratio of 1:20 to obtain a slurry.
[0043] The slurry was coated on copper foil with a coating thickness of 300 μm, dried at 80° C., and then cut into negative electrode sheets of fixed proportions.
[0044] Preparation of secondary batteries: After the negative electrode sheet and NCM positive electrode sheet are stacked and assembled into a dry battery cell, the electrolyte is injected to obtain a lithium battery. The electrolyte is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.0 mol / L.
[0045] Example 2
[0046] Most of the steps in Example 2 are the same as those in Example 1, except for the second binder polymer.
[0047] Sodium allyl sulfonate, hydroxybutyl acrylate, and methacrylamide were reacted in an aqueous solution at a mass ratio of 3:6:4 by free radical polymerization to obtain a random copolymer of sodium allyl sulfonate, methacrylamide, and hydroxybutyl acrylate as a second binder polymer. The synthesis initiator was sodium persulfate, the initiator addition amount was 1.2%, the monomer concentration was 27%, the reaction time was 6.5 hours, the reaction temperature was 70°C, and the molecular weight of the obtained polymer was 75*10 4 , a random second binder polymer with a PDI of 1.37.
[0048] Example 3 to Example 21
[0049] Most of the steps of Examples 3 to 21 are the same as those of Example 1, except that the formula in Table 1 is used.
[0050] Comparative Example 1 to Comparative Example 3
[0051] Most of the steps of Comparative Examples 1 to 3 are the same as those of Example 1, except that the formula in Table 1 is used.
[0052] Comparative Example 4
[0053] Most of the steps of Comparative Example 4 are the same as those of Example 1, except that the negative electrode sheet preparation method is as follows: sodium vinyl sulfonate, SBR, silicon negative electrode, and conductive agent super P are blended in a mass ratio of 1.7:3.3:96:1 to obtain a blended powder, and the powder is blended with deionized water in a ratio of 1:20 to obtain a slurry.
[0054] The molecular weight and distribution of the second binder polymer are tested in accordance with the national standard GB / T 31816-2015.
[0055] Table 1
[0056]
[0057] The negative electrode sheets and secondary batteries prepared in the above examples and comparative examples were subjected to the following tests.
[0058] 1. Film strength and elongation at break:
[0059] Sample preparation method: Spread the second binder polymer glue in a mold with the following dimensions: length * width * depth = 8cm * 1.5cm * 0.5cm; place it in a cool, dry place at room temperature for 2-3 days, then transfer it to a 60°C forced air oven and dry it for 5-10 minutes until it is dry and free of bubbles.
[0060] The dried film was tested using a universal tensile tester. Test conditions: Test speed: 200 mm / min, gauge length: 25.00 mm, test temperature: 25°C, test humidity: 45-55%.
[0061] 2. Negative electrode peeling force test:
[0062] The coated single-sided negative electrode sheet was heated at 2.4 g / cm 3 After compaction, a tensile testing machine with a range of 20N was used. The electrode was cut into 20cm long and 3cm wide. 3M double-sided tape was attached to the steel plate. The electrode coating was fixed on the tape on the steel plate with the surface facing down. After rolling back and forth 6 times with a 2.5kg roller, the coating and copper foil were torn off. The upper plate clamped the copper foil side, stretched at a speed of 50mm / min and 180°C, and the data of the tensile plate stability was recorded as the peel strength (N / m).
[0063] 3. Distribution of adhesive on the negative electrode sheet in the longitudinal direction:
[0064] Thermogravimetric method is used to test the adhesive specific gravity A1 at the bottom of the electrode and the adhesive specific gravity A2 at the top of the electrode. When the A1 / A2 ratio is greater than 1.1, the adhesive floats up. When the A1 / A2 ratio is 0.8<≤1.1, the adhesive is evenly distributed.
[0065] 4. Slurry 200 mesh sieving time:
[0066] Using deionized water as the solvent, a slurry with a solid content of 52% was prepared according to the ratio of graphite:binder = 98:2. 100g of the slurry was sieved with a 200-mesh filter. The sieving time was compared. The shorter the sieving time, the better the dispersibility.
[0067] 5. Let the slurry stand for 24 hours:
[0068] The negative electrode slurry was placed at 25°C for 24 hours, and the viscosity η of the slurry before and after standing was measured. If the viscosity change was greater than 5000mPa·s, it indicated that the static viscosity of the slurry was unstable. The difference in solid content between the upper and lower parts after standing was measured. If M>1%, the slurry settled.
[0069] 6. Normal temperature cycle test:
[0070] After the battery is placed in a constant temperature test room at 25℃±2℃ for 1 hour, it is charged to 3.65V at 1C constant current and constant voltage, with a cut-off current of 0.05C; it is discharged to 2.5V at 1C constant current, and the discharge capacity is recorded; the above steps are repeated 500 times, and the capacity retention rate is calculated.
[0071] The above test results are shown in Table 2 below.
[0072] Table 2
[0073]
[0074] From the test results of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be seen that the ionic units, acrylate units and amide units in the second binder polymer improve the mechanical strength and flexibility of the second binder polymer, thereby improving the electrode peeling force, inhibiting the floating of SBR, and improving the slurry stability. The slurry does not settle when left standing, the slurry screening time is short, the slurry dispersion ability is good, and the battery cycle performance is good.
[0075] From the test results of Examples 1 and 4 to 7, it can be seen that when the mass ratio of the ionic unit to the amide unit / acrylate unit in the second binder polymer is in the range of (1-4): (6-9), the second binder polymer can effectively inhibit the floating of SBR in the negative electrode slurry, prevent the slurry from settling, and the slurry screening time is short and the dispersion is good, which further improves the cycle performance of the battery.
[0076] The test results of Examples 1, 8, and 9 show that when the weight-average molecular weight of the second binder polymer is too high, the viscosity of the slurry increases, which reduces the fluidity of the negative electrode slurry, resulting in uneven electrode coating and poor battery cycling performance. When the weight-average molecular weight of the second binder polymer is too low, the mechanical strength of the second binder polymer decreases, making it susceptible to swelling or degradation by the electrolyte, releasing small molecules and reducing the battery's cycle life.
[0077] From the test results of Example 2 and Example 10-Example 15, it can be seen that when the mass ratio of the ionic unit, the acrylate unit, and the amide unit in the second binder polymer is in the range of (1-4): (2-6): (2-6), the second binder polymer has good mechanical strength and flexibility, thereby improving the electrode peeling force, inhibiting the floating of SBR, and improving the slurry stability. The slurry does not settle when left standing, the slurry screening time is short, the slurry dispersion ability is good, and the battery cycle performance is good.
[0078] It can be seen from the test results of Example 2, Example 16, and Example 17 that when the monomers corresponding to the ionic units, acrylate units, and amide units are selected from other monomer types in this application, the second binder polymer still has good mechanical strength and flexibility, and the negative electrode slurry has good stability, so that the negative electrode sheet has a higher peel strength and the battery has good cycle performance.
[0079] From the test results of Example 2 and Example 18-Example 21, it can be seen that when the mass ratio of the first binder polymer to the second binder polymer is in the range of (0.5-3): (4.5-2), the second binder polymer can better suppress the floating of the first binder polymer and improve the peeling force of the electrode.
[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A negative electrode binder composition, characterized in that The negative electrode binder composition includes a first binder polymer and a second binder polymer, wherein the first binder polymer is styrene-butadiene rubber; The second binder polymer comprises the following structural units: a, an ionic unit; b, an acrylate unit or an amide unit; the mass ratio of the a unit to the b unit is (1-4): (6-9); Alternatively, the second binder polymer comprises the following structural units: a. an ionic unit; b. an acrylate unit and an amide unit; the mass ratio of the ionic unit, the acrylate unit and the amide unit is (1-4): (2-6): (2-6); The weight average molecular weight of the second binder polymer is 5*10 4 -90*10 4 g / mol; The mass ratio of the first binder polymer to the second binder polymer is (0.5-3):(2-3).
2. The negative electrode binder composition according to claim 1, wherein The dispersibility index of the second binder polymer is 1.2-3.
3. The negative electrode binder composition according to claim 1, wherein The ionic unit is a structural unit obtained by polymerization of an ionic monomer containing a double bond and a charge, and the ionic monomer includes one or more of sodium vinyl sulfonate, sodium vinyl phosphate, vinyl imidazole salt, sodium acrylate, sodium allyl sulfonate, dimethylaminoethyl methacrylate, sodium 2-acrylamide-2-methylpropane sulfonate, and methacryloyloxyethyltrimethylammonium chloride.
4. The negative electrode binder composition according to claim 1, wherein The acrylate unit is a structural unit obtained by polymerization of acrylate monomers, and the acrylate monomers include one or more of methyl acrylate, ethyl acrylate, propyl acrylate, isobutyl acrylate, tert-butyl acrylate, butyl acrylate, 2-isooctyl acrylate, lauryl acrylate, octadecyl acrylate, methyl methacrylate, butyl methacrylate, phenyl methacrylate, n-hexyl acrylate, hydroxyethyl acrylate, and hydroxybutyl acrylate.
5. The negative electrode binder composition according to claim 1, characterized in that The amide units are structural units obtained by polymerization of amide monomers, and the amide monomers include one or more of acrylamide, dimethylacrylamide, methacrylamide, caprolactam, isobutoxymethylacrylamide, and diacetone acrylamide.
6. A negative electrode sheet, characterized in that: The invention comprises a negative electrode current collector and a negative electrode active material layer provided on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode binder composition according to any one of claims 1 to 5.
7. A secondary battery, characterized in that: Including the negative electrode sheet according to claim 6.
Citation Information
Patent Citations
Negative electrode binder and preparation method therefor, negative electrode sheet and battery
WO2023143035A1
Binder composition, negative electrode for secondary battery comprising binder composition, and secondary battery comprising negative electrode
WO2024049190A1